2002
DOI: 10.1046/j.1440-1681.2002.03690.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects Of Melanocortins On Cardiovascular Regulation In Rats

Abstract: 1. Of the melanocortin peptides, gamma(2)-melanocyte-stimulating hormone (MSH) has been attributed a cardiovascular effect, inducing an increase in blood pressure and heart rate. Although still controversial, this effect, based on pharmacological blockade experiments, is supposed to be mediated through sympathetic activation. 2. The aims of the present study were to identify the N-terminal pro-opiomelanocortin (N-POMC) fragments and melanocortins that influence blood pressure and heart rate and to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…Numerous earlier studies demonstrated that these cardiovascular responses occurred in conscious, unrestrained rats [15,17,18,[29][30][31][32]. Our study is the first we are aware of to demonstrate the effects of g 2 -MSH in mice, and the only one to show that the responses were almost identical in the same rodent whether anesthetized or conscious (Table 1).…”
Section: Time (Min)supporting
confidence: 55%
See 1 more Smart Citation
“…Numerous earlier studies demonstrated that these cardiovascular responses occurred in conscious, unrestrained rats [15,17,18,[29][30][31][32]. Our study is the first we are aware of to demonstrate the effects of g 2 -MSH in mice, and the only one to show that the responses were almost identical in the same rodent whether anesthetized or conscious (Table 1).…”
Section: Time (Min)supporting
confidence: 55%
“…Both a and g-MSH have been shown to possess effects on the cardiovascular and renal systems: both peptides are natriuretic when infused intravenously or into a renal artery [7][8][9][10], and both cause an increase in mean arterial pressure (MAP) and heart rate [5,11]. In the case of g-MSH, intravenous injections cause a rapid (within seconds) increase in both MAP and heart rate, which is thought to reflect a centrally mediated, shortlasting increase in sympathetic nervous outflow [12,13]; injections into a lateral cerebral ventricle also elevate MAP and heart rate, but over a longer time course [14,15]. On the other hand, a-MSH exhibits no cardiovascular action when given intravenously, but causes sympathoexcitation when administered intracerebroventricularly [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…As previously cited, it has been proposed that high-dose AAS administration could increase a-melanocyte-stimulating hormone levels (Lindblon et al 2003). Thus, an involvement of melanocortin system in AAS-induced autonomic changes may also be suggested, since it has been shown that central administration of melanocotins, in rats, can elicit increases in blood pressure and LF power of blood pressure variability, indicating increased sympathetic activity (Ramaekers et al 2002b). It is known that sympathetic and vagal influences counteract in a manner that a sympathetic hyperactivation state could lead to a decrease in vagal cardiac control or vice versa (Levy 1971).…”
Section: Discussionmentioning
confidence: 99%
“…␥-MSH, a specific MC3R agonist, increases arterial pressure when administered into the CNS in rodents. 11,12 Adult MC3R-deficient (Ϫ/Ϫ) mice have increased adipose mass despite hypophagia and normal metabolic rates but do not have increased body weight compared with wild-type (WT) mice. 13 In contrast, adult MC4R (Ϫ/Ϫ) mice are hyperphagic and are much heavier than WT mice despite severe hyperleptinemia.…”
mentioning
confidence: 99%